KEDUDUKAN DAN PERAN PERHIMPUNAN PEMILIK DAN PENGHUNI SATUAN RUMAH SUSUN (PPPSRS) DALAM PENYELESAIAN SENGKETA PENETAPAN BIAYA PENGELOLAAN DI RUMAH SUSUN SEDERHANA MILIK (RUSUNAMI) (Studi Kasus: Rusunami Kalibata City Jakarta) - Ernawati Ernawati (Jurnal Hukum dan Bisnis (Selisik), 2019)
The existence of unilateral determination the cost of managing electricity, water and street lighting tax carried out by the Kalibata City Simple Housing Management Board is disputed by the residents who are members of the Kalibata City Citizens Community (KWKC). For this reason, the authors highlight the position and role of the Owner Association and the Occupants of the Flat House Unit (PPPSRS) in the legislation concerning the Flats, the responsibilities of the PPPSRS and the role of the Government to address these problems. In the end the writer concludes that PPPSRS as a legal entity that forms and appoints a management body, has not reflected the implementation of its duties and authorities optimally according to the mandate of the Law on Flats. But up to now, the Government has not yet realized the Implementing Regulation of Law Number 20 of 2011 concerning Flats, as a result other derivative regulations related to flats at the local government level have not yet been realized because they are not in accordance with the order of laws and regulations in Indonesia. As a result of legal vacancies related to the absence of Implementing Regulations from Law No. 20 of 2011 concerning Flats, the dispute over the management of flats in Kalibata city flats and in particular the disputes over the management of flats throughout Indonesia has become increasingly chaotic until now.